Financial Process Mining Characteristics - Lopata, Audrius; Butleris, Rimantas; Gudas, Saulius; Rudžionienė, Kristina; Žioba, Liutauras; Veitaitė, Ilona; Dilijonas, Darius; Grišius, Evaldas; Zwitserloot, Maarten (Information and Software Technologies, 2022)
The purpose of this paper is to present continuous results of the research in financial data analysis. Many organizations face challenges by processing a colossal quantity of financial data for evaluation of the current state of the organization, for analysis of future strategies and other purposes. One of the possible ways to analyse financial data is to use process mining techniques. This paper proceeds with analysis and usage of financial data cubes dimensions using General Ledger information of particular organizations in the Netherlands. The research project is funded by European Regional Development Fund according to the 2014–2020 Operational Programme for the European Union Funds’ Investments under measure No. 01.2.1-LVPA-T-848 “Smart FDI”. Project no.: 01.2.1-LVPA-T-848–02-0004; Period of project implementation: 2020–06-01–2022–05-31.